The critical music fan: the role of criticality in collective constructions of brand loyalty. (4th June 2019) - Obiegbu, Chinedu James; Larsen, Gretchen; Ellis, Nick
Abstract : Purpose: The purpose of this paper is to explore how the act of expressing criticism against a music brand fits with the identity and practices associated with being a loyal fan of that brand. Design/methodology/approach: Drawing on insights from theories of brand loyalty and fandom, this interpretive inquiry makes use of data from an online forum dedicated to the band, U2, and interviews with forum members. A combination of online ethnography and discourse analysis is employed. Findings: The findings reveal how interpretations of the act of expressing criticism within a space that ostensibly functions as a place to celebrate all things U2 related, shape the construction of loyalty to the b(r)and in diverse ways. The apparent in-group tensions between being loyal and being critical pose a challenge to the taken for granted nature of brand loyalty and fandom, highlighting the nuanced ways with which they manifest. Originality/value: By examining the role of criticality within otherwise loyal spaces, the authors contribute to brand loyalty theory by revealing the malleability of the concept, as meaning is constantly being reshaped depending on individual realities.